2017
DOI: 10.18203/2320-1770.ijrcog20174016
|View full text |Cite
|
Sign up to set email alerts
|

Timing and reasons for antenatal care booking among women in a tertiary health care center in Southern Nigeria

Abstract: Background: Antenatal care is one of the four pillars of safe motherhood and its benefits in preventing adverse feto-maternal outcome is proven. Commencement of antenatal care early has been shown to be key for this benefit to be fully realized. The aim of this study was to determine the antenatal booking pattern of pregnant women and its determinants in our environment.Methods: A cross sectional study of women attending the booking clinic in the University of Uyo Teaching Hospital, Akwa Ibom State, Southern N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
8
6
0
Order By: Relevance
“…Previous positive pregnancy experiences made pregnant women develop confidence and thus were less motivated to initiate antenatal care early. This is in line with a study that found that multiparous women were usually confident, believing that having delivered many times previously, they were well versed in pregnancy and delivery and did not need to book antenatal care early [23]. On the other hand, previous negative pregnancy outcomes influenced some of the participants to delay initiating antenatal care because initially, they planned to terminate the pregnancy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous positive pregnancy experiences made pregnant women develop confidence and thus were less motivated to initiate antenatal care early. This is in line with a study that found that multiparous women were usually confident, believing that having delivered many times previously, they were well versed in pregnancy and delivery and did not need to book antenatal care early [23]. On the other hand, previous negative pregnancy outcomes influenced some of the participants to delay initiating antenatal care because initially, they planned to terminate the pregnancy.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, some participants believed that there was no ideal booking time for antenatal care. This is similar to a study in southern Nigeria in which the majority of pregnant women claimed that it is safe to book antenatal care at any time during pregnancy [23]. There were diverse reasons for the lack of information on the ideal booking time.…”
Section: Discussionsupporting
confidence: 83%
“…Previous positive pregnancy experiences made pregnant women develop confidence and thus were less motivated to initiate antenatal care early. This is in line with another study that found that multiparous women are usually confident, believing that having delivered many times previously, they are well versed with the art and need not book for antenatal care early [31]. On the other hand, previous negative pregnancy outcomes influenced some of the participants to delay initiating antenatal care because initially they planned to terminate the pregnancy.…”
Section: Perceived Susceptibility/ Perceived Severity Due To Late Antsupporting
confidence: 85%
“…In this study, some participants believed that there was no ideal booking time for antenatal care. This is similar to a study in Southern Nigeria in which the majority of pregnant women claimed that it was safe to book antenatal care at any time during pregnancy [31]. There were diverse reasons for lack of information on ideal booking time.…”
Section: Perceived Susceptibility/ Perceived Severity Due To Late Antsupporting
confidence: 84%
“…In this study, some participants believed that there was no ideal booking time for antenatal care similar to a study in Southern Nigeria in which the majority of pregnant women claimed that it was safe to book antenatal care at any time during pregnancy [40]. There were diverse reasons for lack of 20 information on ideal booking time.…”
Section: Perceived Susceptibility/ Perceived Severity Due To Late Antmentioning
confidence: 52%